Implementação do sistema brasileiro de inspeção de produtos de origem animal (SISBI- POA) em Santa Maria-RS. - Machado, Lidiane Viera (2017)
The hygienic-sanitary and quality-control issues in the elaboration of safe foods have long been a subject incorporated in public health. However, the production and consumption of animal products that are not in compliance with current legal standards, whether due to a lack of adequate legislation or by poor inspection, continue to pose a danger to consumer health. Over the last decade, some major developments have had significant impact on food inspection / control, including the development of food standards and new public policies. Due to the multiplicity of legislation in most developing countries the food industry faces a major threat to survival and growth. Currently in Brazil, the Ministry of Agriculture, Livestock and Food Supply (MAPA) and its federal, state and municipal levels of government, through their Inspection Services (SIF, SIE and SIM) elaborates and enforces technical norms and procedures, carries out sanitary surveillance and ensures hygienic/ sanitary standards of products and by-products of animal origin intended for consumers. There is still an option of the services adhering to the Brazilian System of Animal Origin Products Inspection (SISBI-POA), which increases the flexibility of inspection services in the three spheres of public administration (federal, state and municipal), standardizes the inspection procedures and processes and makes the establishments under municipal inspection able to market their products throughout the national territory. Therefore, the objective of this work was to implement the SISBI-POA in the municipality of Santa Maria-RS. To achieve this, different stages were developed through action research, evolving preliminary studies and situational diagnosis, evaluation of the requirements for adherence of SIM to SISBI-POA and intervention, besides the preparation of documentation and standardization of new procedures. Finally, a model capable of receiving equivalence to the Federal Inspection Service was reached.